Variations in origin of inferior pancreaticoduodenal artery - Kottapalli, Suresh Babu; Potuganti, Mithil; Kumar, Sarangdhar (International journal of health sciences, 2022)
Coeliac trunk and Superior Mesenteric arteries are very much susceptible to variations and were described by Tandler in 1904. Abdominal aorta branches are classified as single double or visceral parietal. Double visceral branches are middle suprarenal, renal and testicular arteries and single visceral branches are coeliac trunk, superior mesenteric and inferior mesenteric arteries. Materials and Methods: After obtaining ethical committee approval, we observed the origin, course and branching pattern of pancreatico duodenal arteries in 50 cadavers kept for dissection from 2019-2022 in Rohilkand Medical College and Hospital and Ayaan Institute of Medical Sciences. Results: In a male cadaver aged approximately 60 years, we observed that inferior pancreatico duodenal artery is absent. In another male cadaver aged about 70 years, we observed an additional inferior pancreatico duodenal artery. In remaining specimens, we observed the branching pattern very much normal.